Micro/nanoscale electrohydrodynamic printing for functional metallic structures. (December 2022) - Meng, Z.; Li, J.; Chen, Y.; Gao, T.; Yu, K.; Gu, B.; Qu, M.; Li, X.; Lan, H.; Li, D.; He, J.
Abstract: Metallic additive manufacturing (AM) techniques have substantially liberated the architectural design philosophy of macro/mesoscale functional structures from ease of manufacturing to optimization of performance. However, the application of most metallic AM strategies is limited by their low adaptability and high costs in fabricating micro/nanoscale structures that are increasingly demanded in the electronics field. As an emerging and promising metallic AM technology, electrohydrodynamic (EHD) printing relies on the electrostatic force to facilitate the precise deposition of ultrafine droplets or fibers derived from different metallic materials, providing a revolutionary and versatile strategy to fabricate micro/nanoscale metallic architectures. Here we focus on the state-of-the-art developments of metallic EHD printing for micro/nanoscale functional architectures as well as their potential applications. The basic principles, typical setups, working modes, and critical process parameters of micro/nanoscale metallic EHD printing are analyzed. Various metallic inks including nanoparticles and precursors for micro/nanoscale EHD printing are surveyed in terms of ink compositions, minimum feature sizes, as well as post-treatment strategies to achieve specific functionalities. More importantly, we highlight the unique capabilities of micro/nanoscale metallic EHD printing in fabricating minuscule 3D electronic structures, high-resolution multimaterial architectures, high-performance sensing structures, multi-functional optoelectronic components, etc . Finally, major challenges and future perspectives are discussed to translate micro/nanoscale EHD printing into a mature AM technology for the fabrication of 3D functional metallic architectures. Graphical abstract: Image 1